An outbreak of tuberculosis due to Mycobacterium bovis infection in a pack of English Foxhounds (2016–2017). Issue 6 (30th July 2018) - O'Halloran, Conor; Hope, Jayne C.; Dobromylskyj, Melanie; Burr, Paul; McDonald, Kieran; Rhodes, Shelley; Roberts, Tony; Dampney, Richard; De la Rua‐Domenech, Ricardo; Robinson, Nicholas; Gunn‐Moore, Danielle A.
Abstract: Mycobacterium bovis can cause tuberculosis (TB) in social mammals including lions, cattle and man, but canine infections are considered rare. In 2016/17 we investigated a M. bovis TB outbreak in a pack of approximately 180 Foxhounds within the bovine TB Edge Area of England. We employed a combination of immunological tests including an interferon gamma release assay (IGRA) and a serological assay (DPP VetTB, Chembio). Test‐positive hounds were euthanased and subjected to post‐mortem examination (PME). Overall 164 hounds were tested; 97 (59%) responded positively to at least one test. Eighty‐five (52%) dogs responded to M. bovis antigens by IGRA while only 21 (12.9%) had detectable serological responses. At PME three hounds (3.1%) had visible lesions (VL) due to M. bovis infection, later confirmed by culture. Samples from 24 non‐VL hounds were cultured and M. bovis infection was confirmed in a further three hounds (11%). This study is the first investigation and report of an outbreak of M. bovis TB in a canine species. We establish that, in principle, diagnostic tests used for identifying infected individuals of other species can effectively be used in the dog. Further work is urgently needed to establish the sensitivity and specificity of the testing approach used in this study for future clinical application.